2007
DOI: 10.1179/016164107x172248
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin suppresses lipopolysaccharide-induced expressions of cyclooxygenase-2 and inducible nitric oxide synthase in mouse BV2 microglial cells

Abstract: These results show that amygdalin exerts anti-inflammatory and analgesic effects and it dose so probably by suppressing the mRNA expressions of COX-2 and iNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Fruit-derived amygdalin is a naturally occurring glycoside with broad biological activities such as anticancer, antiatherosclerosis, anti-inflammation and immunomodulation [15][16][17][18]. Little is known about its effect on neuronal survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit-derived amygdalin is a naturally occurring glycoside with broad biological activities such as anticancer, antiatherosclerosis, anti-inflammation and immunomodulation [15][16][17][18]. Little is known about its effect on neuronal survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1A) is one of the main active components in S. persicae as well as the seeds of other Rosaceae family members [14]. Amygdalin exerts a range of pharmacological activities for the treatment of cancer, asthma, hypertension, migraine, atherosclerosis and chronic inflammation [15][16][17][18]. Importantly, it was recently reported that amygdalin could reduce ischemic brain injury via regulating cerebrocellular energy metabolism [19].…”
Section: Introductionmentioning
confidence: 99%
“…Amygdalin, a cyano-containing glycoside compound widely found in the seed of Rosaceae (Todorova, Pesheva, Iliev, Bardarov, & Todorova, 2017), is an active ingredient in bitter almonds. Its pharmacological effects are extensive, mainly including relief of cough and phlegm, and immunosuppressive (Hwang, Lee, Kim, Shim, & Hahm, 2008), immunomodulation, anti-inflammatory (Yang et al, 2007), antitumour (Makarevic et al, 2014), and anti-atherosclerosis activities (Jiagang et al, 2011). Amygdalin is a very popular anticancer adjuvant in Europe and America (Milazzo, Lejeune, & Ernst, 2007).…”
mentioning
confidence: 99%
“…Amygdalin is also present in several other related species such as apples, apricots, almonds, cherries, plums, and peaches [2830]. Previous studies have demonstrated that amygdalin exhibited a wide range of biological activities including anti-inflammatory, anticancer, antihypertension, and antiatherosclerosis activities [27, 31–33]. However, the neurotrophic effect of amygdalin has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%